Evolution Of The Women Images In Chi Li’s Novel - Mariana Mariana (Bina Nusantara University, 2012)
Chi Li, one of the outstanding women writers in the 1980’s, portrays various images of women in her works. Female image that Chi Li describe is from obedient to tradition type until self determination and independence, and gain a clairvoyance of that female’s culture existence state and the value conception separately. Chi Li thinks deeply of the meaning of Chinese female’s life, in search of the culture value of contemporary female throughout the different female images, which figured in the novel, and it revealed the sprits in exploring of culture and the unique aesthetics taste of the author.